2004
DOI: 10.1007/s00445-004-0359-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental constraints on degassing and permeability in volcanic conduit flow

Abstract: This study assesses the effect of decompression rate on two processes that directly influence the behavior of volcanic eruptions: degassing and permeability in magmas. We studied the degassing of magma with experiments on hydrated natural rhyolitic glass at high pressure and temperature. From the data collected, we defined and characterized one degassing regime in equilibrium and two regimes in disequilibrium. Equilibrium bubble growth occurs when the decompression rate is slower than 0.1 MPa s -1 , while high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
118
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 36 publications
10
118
2
Order By: Relevance
“…These vesicles provide an indirect record of magma ascent conditions. A significant body of work has been aimed at using bubble number density and size distributions to constrain rates of eruptive magma ascent and the timing of gas exsolution (e.g., Mangan et al 1993;Cashman and Mangan 1994;Polacci et al 2003;Burgisser and Gardner 2005;Proussevitch et al 2007). Vesicle shape is another manifestation of magma ascent conditions, in particular bubble growth, coalescence, and shearing (e.g., Klug and Cashman 1996;Mangan and Cashmann 1996;Polacci et al 2003;Rust et al 2003;Okumura et al 2008;Wright and Weinberg 2009), and can therefore provide a valuable complement to conventional studies of pyroclast textures.…”
Section: Introductionmentioning
confidence: 99%
“…These vesicles provide an indirect record of magma ascent conditions. A significant body of work has been aimed at using bubble number density and size distributions to constrain rates of eruptive magma ascent and the timing of gas exsolution (e.g., Mangan et al 1993;Cashman and Mangan 1994;Polacci et al 2003;Burgisser and Gardner 2005;Proussevitch et al 2007). Vesicle shape is another manifestation of magma ascent conditions, in particular bubble growth, coalescence, and shearing (e.g., Klug and Cashman 1996;Mangan and Cashmann 1996;Polacci et al 2003;Rust et al 2003;Okumura et al 2008;Wright and Weinberg 2009), and can therefore provide a valuable complement to conventional studies of pyroclast textures.…”
Section: Introductionmentioning
confidence: 99%
“…The products of these lower pressure runs also have more distorted and elongated bubbles, as opposed to the smaller rounded ones at higher pressures. Burgisser and Gardner (2004) (Burgisser and Gardner, 2004). In our runs, the rhyodacite charges did not contain an added fluid, and so collapse could occur.…”
Section: Decompression Experimentsmentioning
confidence: 72%
“…Most recently, Burgisser and Gardner (2004) found a threshold at ~40 vol.%. In addition, Burgisser and Gardner (2004) found that the onset of permeability is not instantaneous, but takes on order of 180 seconds when high-silica rhyolite reaches that threshold. Those 180 seconds likely represent the amount of time required for complete networks of bubbles to connect.…”
Section: Degassing During Magma Ascent In the Conduitmentioning
confidence: 99%
See 2 more Smart Citations